Rundfunkbeitragsbefreiung: Ineffizient, anreizfeindlich und ungerecht - Holger Cischinsky; Joachim Kirchner (Wirtschaftsdienst, 2014)
Nach der Umstellung der geräteabhängigen Rundfunkgebühren zu einem Rundfunkbeitrag pro Wohnung ist die Beitragsbefreiung der Mindestsicherungsempfänger geblieben. Hierdurch entstehen Grenzfälle, die mit negativen Anreizen verbunden sind. Die Autoren fordern daher, dass der Rundfunkbeitrag der Grundsicherung zugeschlagen wird und nicht der ARD ZDF Deutschlandradio Beitragsservice die Bedürftigkeit prüfen muss. – – In Germany, recipients of social assistance transfers and of long term unemployment benefits (Arbeitslosengeld II) are exempted from paying contributions to public service broadcasting. But this exemption brings about allocative inefficiencies by creating negative incentives for the recipients to avoid or to reduce the need for help and by causing needless administrative efforts. Furthermore, the exemption from payment of contributions is questionable with regard to distributional goals. It would therefore be better to raise benefits by the amount of the contribution to public service broadcasting and to cancel the exemption.
Keywords: H24; H31; H55; 330; Rundfunkfinanzierung; Subvention; Anreiz; Deutschland